A study on the shielding integrity and effectiveness of an enclosure - Sanya, Sekhar. (2013)
With the growing use of electronic products at home and at industries, research is required to ensure that EMC requirements set by FCC are met. This can be challenge without a shielding enclosure. Even with an enclosure in place, the shielding effectiveness can be compromised by slots, apertures, which are used for heat dissipation, cables and displays.